BE_ZIVILSTRAF BK 2017 280 vom 28. September 2017 - BE Obergericht (2017)
Nichtanhandnahme Strafverfahren wegen (Nacht-)Ruhestörung, Sachbeschädigung, \"Hackerangriff\" etc. | Einstellung/Nichtanhandnahme